The Use of Student Engagement Findings as a Case of Evidence‐Based Practice. Issue 178 (June 2017) - Kinzie, Jillian
Abstract : The chapter considers student engagement to discuss the use of assessment evidence to advance evidence‐based practice and to illustrate a scholarship of practice.